Gastrointestinal Helminth Infections in Dogs in Sheep and Goat Farms in Greece: Prevalence, Involvement of Wild Canid Predators and Use of Anthelmintics - Eleni I. Katsarou; Konstantinos V. Arsenopoulos; Charalambia K. Michael; Daphne T. Lianou; Efthymia Petinaki; Elias Papadopoulos; George C. Fthenakis (Animals)
The objectives of the present work were the investigation of gastrointestinal parasitic infections in dogs in small ruminant farms in Greece, the elucidation of potential predictors for these infections and the description of practices related to administration of anthelmintics to dogs. This study was carried out in 444 small ruminant farms in Greece. Faecal samples were collected directly from the rectum of the dogs in the farms. The samples were processed by means of conventional parasitological techniques, specifically, a combined sedimentation flotation technique. There were dogs in 92.8% of the farms, with a median number of four dogs per farm. The following variables were associated with the presence of dogs in the farms: the presence of wild mammal predators near the farms, the increased daily period of farmers’ presence at the farm, goats as the livestock species at the farm and the management system applied in the farm. Helminth eggs were detected in samples from 72.6% of the farms. The main helminth eggs detected were those of hookworms (Uncinaria/Ancylostoma) and Toxocara canis, in 68.6% and 51.3% of the farms, respectively. In our multivariable analyses, an association emerged between the presence of canid predators near a farm and the detection of these helminths in faecal samples: in 76% and 60% of the samples, respectively, versus in 58% and 39% of the samples from farms with no canid presence. Of farmers with dogs, 16.0% reported that they omitted the administration of anthelmintics to the animals. In multivariable analysis, the semi-extensive or extensive management system applied in the farm, the lower annual milk production per animal and the lack of collaboration with a veterinary practice were the significant predictors for the omission of anthelmintic administration to the farm dogs. There was also a clear association in the omission of anthelmintic administration to the dogs and to the livestock on the farm. The most frequently administered anthelmintic was praziquantel, which was used in 93.6% of the farms.